Facile and controllable fabrication of multifunctional nanohybrid films composed of reduced graphene oxide and titanium dioxide through layer-by-layer assembly - Kim, Young-Kwan; Jang, Hongje; Kang, Kyungtae (ELSEVIER SCIENCE SA, 2017)
A facile fabrication strategy of multi-functional hybrid thin films of reduced graphene oxide (RGO) and TiO2 was developed by using layer-by-layer (LBL) assembly of titanium(IV) bis(ammonium lactato) dihydroxide (TALH) and polyallylamine grafted reduced graphene oxide (PAA-RGO) as negatively and positively charged components. The fabrication process of hybrid films was thoroughly characterized by using UV-vis spectroscopic, ellipsometric and atomic force microscopic analysis. This fabrication strategy provided precisely-controlled thickness, surface roughness through 1-10 LBL assembly cycles. By thermal treatment, the PAA-RGO and TALH in the hybrid films were respectively converted into RGO and TiO2 with the restoration of their electrical conductivity, UV-resistance and photo-catalytic self-cleaning properties. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: LASER DESORPTION/IONIZATION; MULTILAYER FILMS; SMALL MOLECULES; GRAPHITE OXIDE; HYBRID FILMS; REDUCTION; POLYALLYLAMINE; CONDUCTIVITY; TRANSPARENT; NANOWIRES